2002
DOI: 10.1111/j.1746-1049.2002.tb00924.x
|View full text |Cite
|
Sign up to set email alerts
|

STRUCTURAL CHANGES AND SPECIALIZATION IN BRAZILIAN INDUSTRY: THE EVOLUTION OF LEADING COMPANIES AND THE M&A PROCESS

Abstract: This paper analyzes changes in the Brazilian productive structure and in ownership structures of leading companies during the 1990s. It uses information from balance sheets published in Gazeta Mercantil and from the Thomson Financial Securities Data database on M&A. The main findings are: (i) the sectoral distribution of leading companies has remained stable; (ii) there has been a strong change in the ownership structure in Brazil, with an increase in the participation of multinational enterprises (MNEs) in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
3

Year Published

2002
2002
2015
2015

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 2 publications
0
3
0
3
Order By: Relevance
“…The share of Brazilian industry in the economy did not change throughout the 1990s (Rocha and Kupfer, 2002). Among the different industrial groups (table 1), industrial commodities, durable goods and food and beverages showed a better performance due to the income effect generated by the Plano Real (in the case of durable goods and food and beverages) and/or better terms of trade and export performance (industrial commodities and durable goods).…”
Section: Industrial Performancementioning
confidence: 96%
“…The share of Brazilian industry in the economy did not change throughout the 1990s (Rocha and Kupfer, 2002). Among the different industrial groups (table 1), industrial commodities, durable goods and food and beverages showed a better performance due to the income effect generated by the Plano Real (in the case of durable goods and food and beverages) and/or better terms of trade and export performance (industrial commodities and durable goods).…”
Section: Industrial Performancementioning
confidence: 96%
“…En la Argentina, la participación extranjera en las ventas totales de las 200 más grandes empresas manufactureras aumentó del 43% en 1994 al 69% en 1998 (Kulfas, Porta y Ramos, 2002). En el Brasil, entre las 300 empresas más grandes del país, las multinacionales incrementaron su participación en las ventas del 14,8% al 36,4% (Rocha y Kupfer, 2002). El movimiento de capital se dirigió principalmente hacia la adquisición de bienes existentes, a través de la privatización, las fusiones y las adquisiciones.…”
Section: Reformas Estructurales: Destrucción Y Resurgimientounclassified
“…a) Igual estructura productiva con menos trabajadores La participación de la industria brasileña en la economía no se modificó en la década de 1990 (Rocha y Kupfer, 2002). Entre los diferentes grupos de industrias (cuadro 1), las de productos básicos industriales, de bienes durables y de alimentos y bebidas mostraron resultados mejores: en el caso de los bienes durables y de los alimentos y bebidas, debido al efecto-ingreso generado por el Plan Real, y en el caso de los productos básicos industriales y bienes durables, gracias a mejores términos de intercambio y expansión de las exportaciones.…”
Section: Desempeño De La Industriaunclassified
“…Según Rocha y Kupfer (2002), entre las 300 empresas más grandes del país, las estatales redujeron su participación en el mercado (por ventas) de 44,6% en 1991 a 24,3% en 1999; las transnacionales aumentaron esa participación de 14,8% a 36,4% y las empresas de capital local mantuvieron su posición. Los autores señalan que los cambios en la propiedad de las principales empresas se produjeron en dos etapas.…”
Section: Productos Básicos Agrícolasunclassified